In defence of witches : why women are still on trial - Chollet, Mona, 1973- (London : Picador, 2022)
"Whether selling grimoires on Etsy, posting photos of their crystal-adorned altar on Instagram, or gathering to cast spells on Donald Trump, witches are everywhere. But who exactly were the forebears of these modern witches? Who was historically accused of witchcraft, often meeting violent ends? What types of women have been censored, eliminated, repressed, over the centuries? Mona Chollet takes three archetypes from historic witch hunts, and examines how far women today have the same charges levelled against them: independent women; women who choose not to have children; and women who reject the idea that to age is a terrible thing. Finally, Chollet argues that by considering the lives of those who dared to live differently, we can learn more about the richness of roles available, just how many different things a woman can choose to be"--Publisher's description.
Introduction: their descendants -- A life of one's own: the scourge of women's independence -- Wanting sterility: the no-child option -- The dizzy heights: shattering the image of the 'Old Hag' -- Turning the world upside down: war on nature; war on women.
Translated from the French.
boek
Keywords: Feminism; Witches -- Violence against -- History; Male domination (Social structure); Sex discrimination against women; Sexism; Sexism in witchcraft trials -- History; Witches